Effect of information load and time on observational learning - Breslin, G.; Hodges, N. J.; Williams, A. M. (Research Quarterly for Exercise and Sport, 2009)
We examined whether altering the amount of and moment when visual information is presented affected observational learning for participants practicing a bowling skill. On Day 1, four groups practiced a cricket bowling action. Three groups viewed a full-body point-light model, the model's bowling arm, or between-limb coordination of the model's left and right wrists only. Following retention tests on Day 2, all participants practiced after viewing a full-body display. Retention was again tested on Day 3. Bowling accuracy improved in all four practice groups. Kinematics of the bowling arm became more like the model for the full-body and intralimb groups only. All groups improved on measures of interlimb coordination. Visual search data indicated that participants mainly focused their gaze on the model's bowling arm. These data lead to the suggestion that viewing "end-effector" information (i.e., information pertaining to the bowling arm) is an important perceptual constraint early in observational learning. Implicit manipulations designed to increase attention to other sources of information did not facilitate the learning process.